Dispersion model and impact assessment of Landing and Take Off (LTO) activity at New Yogyakarta International Airport using Aermod - Salsabila Mulya; Suherman Suherman; Taufik Abdillah Natsir (Institut Teknologi Dirgantara Adisutjipto, 2023)
Pollutant dispersion modeling in around Yogyakarta International Airport wasconducted using AERMOD software. There is a strong positive correlation between the number of aircraft and land transportation and the number of pollutants considered. The ambient air quality at the study site for all pollutants originating from the landing and take-off (LTO) cycle is still below quality standards, but for those sourced from the combination of the LTO cycle and land transport traffic for NO2 pollutants exceed the quality standard, while for CO and hydrocarbon pollutants it is still below quality standards.